Dancing in the desert: electronic dance music festivals, carnivalesque rhetorics of disorientation, and performative participant observation - Herring, Kristen D., author; Vasby Anderson, Karrin, advisor; Gibson, Katie, committee member; Aoki, Eric, committee member; Pippen, John, committee member (Colorado State University. Libraries, 2022)
Electronic dance music (EDM) creates communities whose members negotiate and renegotiate the politics of public performances of identity. In this dissertation, I ask "How do EDM festivals function as temporary communities that rhetorically construct the performance of gender and sexuality?" I argue that EDM uses a rhetorical strategy I call disorientation. I detail the ways disorientation helps EDM festival attendees, known as "ravers" or "festies," inhabit liminal spaces and transgress the patriarchal, heteronormative, white supremacist, and capitalist expressions of gender and sexuality that are dominant in the outside world via rhetorics of the carnivalesque. I also develop an approach to rhetorical field methods I call Performative Participant Observation. I demonstrate Performative Participant Observation in this dissertation and argue that similar methods would be useful for scholars interested in studying ephemeral and public performances of gender and sexuality as well as performances of the carnival.